Knowledge management in environmental education:Case studies in environmental education programs in brazilian universities - Escrivão, Giovana [UNESP]; Nagano, Marcelo (My University, 2014)
Although the importance of knowledge management for any organizational environment as a strategy to confront the current instability has been widely recognized, little is known concerning the creation of organizational knowledge. Different contexts that knowledge management can be applied providing creation of new knowledge and its better use, like in the environmental education on accounting of growing environmental degradation. The present paper analyzes and describes the process of knowledge creation in environmental education programs at the two largest Brazilians public universities by conducting comparative case studies. This research can be classified as qualitative with a descriptive characteristic conducted through case studies, as a detailed study of the characteristics of the environmental education programs was realized in two major Brazilian universities. The methods used to collect and analyze the data were interviews and content analysis. At the end of the study it was made some suggestions of practices that can provide manage of the environmental knowledge and incentive for the creation of new knowledge to environmental education programs, as replacing the teams, that are homogeneous, by heterogeneous teams in order to share different contexts, know-how and knowledge. Concerning theory of knowledge creation, some results of studied cases made available the identification of eight observations that question some assumptions of this theory, as the high turnover or the guaranteed stability on work can perform on employees’ commitment to knowledge creation.
Gestão do conhecimento na educação ambiental: Estudo de casos em programas de educação ambiental em universidades brasileiras
Keywords: Environmental education; Environmental education programs; Information; Knowledge; Knowledge creation; Knowledge management; Universities